Solar disinfection of drinking water using flat-plate solar collector - Donasco, Edgar Alan A. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2000)
Inaccessibility to steady supply of safe drinking water remains a problem for developing countries like the Philippines. A treatment method that is simple, low-cost, effective, and sustainable needs to be in place as an alternative. Solar disinfection process for drinking water is a method that is applicable in a household or institutional level. The technology is simple, reliable and operationally cheap for it requires only energy from the sun to run it. Synergetic action of both heat and radiation (UV-A) from the sun is potent in inactivating and destroying pathogenic microorganisms present in water. This study assessed the local suitability of the solar disinfection process through testing a fabricated Solar Disinfection (SODIS) Plant. The set-up basically consisted of the raw and treated water tanks, solar reactor for combined heating and irradiation, and piping accessories. Tests for thermal and microbiological performance proved that solar disinfection through the SODIS Plant is a viable option for water disinfection. Setting the water temperature to at least 50ºC resulted to complete inactivation of Total coliform microorganisms. On an average sunny day, the SODIS Plant is able to raise the water temperature to its minimum effective setting within about 2 hours. Operating at an average of 22% net thermal efficiency, the plant is able to generate 20 liters/m2/day.